STUDY OF THE POTENTIAL DEVELOPMENT OF BIOMASS BASED ELECTRICITY BAMBOO - Aisman Aisman (Jurnal Agroindustri, 2016)
The purpose of this research was to calculate the level of public access to electricity, the number of districts that have not been electrified, searching for the cause of the electrical limitations, analyze the potential development of biomass-based electricity bamboo. This research was conducted by collecting and analyzing secondary data (exploratory). The results showed that an area where the level of public access in the Mentawai Islands to electricity is still low at 21.7%, while the average of West Sumatra has reached 73.5%. There are three districts that have not been electrified the District Siberut Southwestern, Central and Siberut Siberut West. Cause limitation is the limited electrical power supplied by PLN because they rely on diesel power and the difficulty of distributing electricity for people living in remote locations and lack of infrastructure. The development of biomass-based power relative bamboo suitable to be developed in this area, because of the development of the bamboo plant is feasible, and supported by land suitability and size of the area that can be planted. Electrification technology-based biomass (bamboo) can be applied to spots or per region around the bamboo plants are developed.